Dental eruption and growth in Hyracoidea (Mammalia, Afrotheria). Issue 3 (4th May 2017) - Asher, Robert J.; Gunnell, Gregg F.; Seiffert, Erik R.; Pattinson, David; Tabuce, Rodolphe; Hautier, Lionel; Sallam, Hesham M.
ABSTRACT: We investigated dental homologies, development, and growth in living and fossil hyracoids and tested if hyracoids and other mammals show correlations between eruption patterns, gestation time, and age at maturity. Unlike living species, fossil hyracoids simultaneously possess replaced P1 and canine teeth. Fossil species also have shorter crowns, an I3/i3, I2, and a hypoconulid on m3. Prenatal specimens of the living Procavia capensis and Heterohyrax brucei show up to three tooth buds posterior to dI1 and anterior to the seven upper cheek teeth that consistently erupt; erupted teeth include an anterior premolar but not a canine. Most lower cheek teeth finish eruption during growth in hyracoids, not after growth as in most other afrotherians. All hyracoids show the m1 at (lower) or near (upper) the beginning of eruption of permanent teeth; M3/m3 is the last permanent tooth to erupt. The living P. capensis erupts most lower antemolar loci before m2. In contrast, fossil hyraxes erupt lower antemolars after m2. Although the early eruption of antemolars correlates with increased gestation time and age at maturity in primates and Tupaia (i.e., 'Schultz's rule'), and although modern hyraxes resemble some anthropoid primates in exhibiting long gestation and eruption of antemolars at or before molars, eruption patterns do not significantly covary with either life history parameter among afrotherians sampled so far. However, we do observe a shift in eruption timing and crown height in Procavia relative to fossil hyracoids, mirroring observations recently made for other ungulate-grade mammals. SUPPLEMENTAL DATA—Supplemental materials are available for this article for free at www.tandfonline.com/UJVP Citation for this article: Asher, R. J., G. F. Gunnell, E. R. Seiffert, D. Pattinson, R. Tabuce, L. Hautier, and H. M. Sallam. 2017. Dental eruption and growth in Hyracoidea (Mammalia, Afrotheria). Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2017.1317638.